Case report: Reversible splenial lesion syndrome caused by diquat poisoning - Dai, Ping; Sun, Jin; Yu, Zhongkai; Zhang, Tongyue; Wen, Zixin; Jian, Tianzi; Guo, Lanlan; Genjiafu, Aerbusili; Kan, Baotian; Zhang, Binbin; Jian, Xiangdong (Frontiers in Neurology, 2023)
Diquat (DQ), chemically known as 1,1 ‘-ethylene-2,2’ -bipyridine, is a non-selective herbicide for leaf removal and drying. It has toxic effects on central nervous system cells, and toxic neurological lesions include axonal degeneration and pontine myelolysis. At the same time, DQ can also affect the activity of dopaminergic nerve cells through oxidative stress, causing degeneration and reducing dopamine uptake. With the increasing application of DQ in agricultural production, the clinical reports of neurotoxicity caused by acute DQ poisoning are also increasing. At present, DQ rapid-phase-related toxic encephalopathy mainly involves the pons, midbrain, basal ganglia, thalamus and other brain regions. However, this case is unusual in that the lesion mainly involved the splenium of the corpus callosum. It is also the first time to be reported.